Strong Reset Fuzzy Automata (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Strong necks, strong trap, strong trap-reset fuzzy automata and strong mergeable are introduce. We prove that strong neck is non-empty then it is subautomata and prove that if strong neck exists, then it is kernel.